Postneonatal care pathways and the identification of deafness. Issue 1 (18th October 2011) - Watkin, Peter
Abstract : Background: The need to maintain clinical pathways for the postneonatal identification of deafness was investigated following the successful implementation of universal newborn hearing screening. Methods: Identification routes were compared for 378 hearing impaired children ascertained from three 10-year cohorts: one that had not received neonatal screening, one that had received targeted neonatal screening and one that was universally screened. The presence of risk factors was determined in those with a hearing impairment. Results: The cohort comparison confirmed significant changes in the yield from all identification routes apart from referrals reactive to parental or professional concerns. In the cohort universally screened, this reactive yield was 1.23/1000 with 51% having risk factors for deafness. Universal newborn hearing screening did not reduce this postneonatal yield. Conclusions: Despite the successful implementation of newborn hearing screening, clinical pathways with access to audiological assessment need to be maintained within a universal Healthy Child Programme.